2013
DOI: 10.1007/s10096-013-1949-y
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010

Abstract: This study investigated the in vitro susceptibilities of methicillin-resistant Staphylococcus aureus (MRSA) to nine antimicrobial agents in Taiwan. A total of 1,725 isolates were obtained from 20 hospitals throughout Taiwan from 2006 to 2010. The minimum inhibitory concentrations (MICs) of the nine agents were determined by the agar dilution method. The MICs of mupirocin and tyrothricin were determined for 223 MRSA isolates collected from 2009 to 2010. For vancomycin, 99.7 % were susceptible; however, 30.0 % (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…29 Chen et al, 30 studied the susceptibility MRSA to nine antimicrobial agents, it was found that, among these MRSA isolates, 99.7% were susceptible to vancomycin; however, 30.0% (n= 517) exhibited MICs of 2 mg/L and six (0.3%) were intermediately susceptible (VISA, MICs of 4μg/ml) to vancomycin. 30 Many virulence factors are associated with MRSA that enable them to cause disease. 8 In our study, the MRSA strains were produced more lecithinase and protease DNase, coagulase and had more hemolysis activity on blood agar as compared to MSSA isolates which may influenced the pathogenicity of these strains and severity of infections.…”
Section: Discussionmentioning
confidence: 99%
“…29 Chen et al, 30 studied the susceptibility MRSA to nine antimicrobial agents, it was found that, among these MRSA isolates, 99.7% were susceptible to vancomycin; however, 30.0% (n= 517) exhibited MICs of 2 mg/L and six (0.3%) were intermediately susceptible (VISA, MICs of 4μg/ml) to vancomycin. 30 Many virulence factors are associated with MRSA that enable them to cause disease. 8 In our study, the MRSA strains were produced more lecithinase and protease DNase, coagulase and had more hemolysis activity on blood agar as compared to MSSA isolates which may influenced the pathogenicity of these strains and severity of infections.…”
Section: Discussionmentioning
confidence: 99%
“…According to the researches from Taiwan, nemonoxacin demonstrated activity superior to levofloxacin against CA-MRSA isolates, but similar to moxifloxacin and gemifloxacin 5. Nemonoxacin had slightly lower MIC 90 (1 mg/L) for CA-MRSA than ceftobiprole, vancomycin, teicoplanin, and linezolid (2 mg/L, respectively), but higher than daptomycin (0.25 mg/L), tigecycline (0.5 mg/L), and mupirocin (0.25 mg/L) 6,8. However, nemonoxacin had limited activities against vancomycin-intermediate MRSA (MIC ≥0.5 mg/L for 66% [33/50] isolates, MIC 90 =2 mg/L) and daptomycin nonsusceptible MRSA 5…”
Section: Pdmentioning
confidence: 94%
“…Thus, NEMO has a higher barrier for generating resistant pathogens compared to other fluoroquinolones. In vitro resistance to NEMO develops slowly and difficultly via multiple-step mutations [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…NEMO has shown broad spectrum activity both in vitro and in vivo against Gram-positive and Gram-negative bacteria [25][26][27][28][29][30], particularly multi-drug resistant Gram-positive bacteria such as PRSP and MRSA. NEMO also exhibits potent antibacterial activity against Gram-negative bacteria and atypical pathogens such as H. influenzae, M. catarrhalis, M. pneumoniae, C. pneumoniae, and L. pneumophila in vitro [26,31].…”
Section: Introductionmentioning
confidence: 99%